Short-term molecular and cellular effects of ischemia/reperfusion on vascularized lymph node flaps in rats - Frueh, Florian S. (PLoS One, 2020)
Vascularized lymph node (VLN) transfer is an emerging strategy to re-establish lymphatic drainage in chronic lymphedema. However, the biological processes underlying lymph node integration remain elusive. This study introduces an experimental approach facilitating the analysis of short-term molecular and cellular effects of ischemia/reperfusion on VLN flaps. Lymph node flaps were dissected pedicled on the lateral thoracic vessels in 44 Lewis rats. VLN flaps were exposed to 45 or 120 minutes ischemia by in situ clamping of the vascular pedicle with subsequent reperfusion for 24 hours. Flaps not exposed to ischemia/reperfusion served as controls. Lymph nodes and the perinodal adipose tissue were separately analyzed by Western blot for the expression of lymphangiogenic and angiogenic growth factors. Moreover, morphology, microvessel density, proliferation, apoptosis and immune cell infiltration of VLN flaps were further assessed by histology and immunohistochemistry. Ischemia for 120 minutes was associated with a markedly reduced cellularity of lymph nodes but not of the perinodal adipose tissue. In line with this, ischemic lymph nodes exhibited a significantly lower microvessel density and an increased expression of VEGF-D and VEGF-A. However, VEGF-C expression was not upregulated. In contrast, analyses of the perinodal adipose tissue revealed a more subtle decrease of microvessel density, while only the expression of VEGF-D was increased. Moreover, after 120 minutes ischemia, lymph nodes but not the perinodal adipose tissue exhibited significantly higher numbers of proliferating and apoptotic cells as well as infiltrated macrophages and neutrophilic granulocytes compared with non-ischemic flaps. Taken together, lymph nodes of VLN flaps are highly susceptible to ischemia/reperfusion injury. In contrast, the perinodal adipose tissue is less prone to ischemia/reperfusion injury.